SIKAP MASYARAKAT FORAMADIYAHI TERHADAP BAHASA TIDORE (SUATU TINJAUAN SOSIOLINGUISTIK) - Maulud, Ismail; Muhammad, Ikmal (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study aims to determine how the attitude of the Foramadiyahi community towards Tidore language as their mother tongue. The method in this study uses a qualitative descriptive method with data collection using observation and interview techniques. From the results of data analysis, it shows that the Tidore language is the first language for the Foramadiyahi community and as the language of their ancestors who lived in the village of Afa-afa at Tidore island. Tidore language reflects the identity of Tidore tribe. Therefore, the Tidore language needs in daily communication for the Foramadiyahi community. A good language attitude is to always care and feel proud to use the Tidore language in daily life. Besides that, another positive attitude is to always get used to using the Tidore language among other Tidore tribes in Foramadiyahi and outside Foramadiyahi. Then have a high willingness to preserve it by teaching the Tidore language to teenagers and children so that they are also proud to have Tidore as their mother tongue.